RUMAH ADAT SIWALUH JABU DESA BUDAYA LINGGA DI KABUPATEN KARO SEBAGAI WARISAN BUDAYA INTANGIBLE - Aisyah Zalfaa Ar Rahma,; Lila Pelita Hati,; Laura Financia,; Nurhabsyah, (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2023)
A traditional house is one of the inheritances by a tribe or clan to generations. Each traditional house in Indonesia has its own characteristics and has different meanings and uses. In Karo, North Sumatra, Siwaluh Jabu is a traditional house filled with 8 families. Inside this house there are rules that must be followed by all members of the house. The cultural heritage place of this Siwaluh Jabu house is located right in Lingga Village. However, of the dozens of traditional houses, only two remain, one of which is still occupied by several families. Siwaluh Jabu traditional house tourism in this area also cooperates with the government and foreign parties. However, the condition of the traditional house and its surroundings remains poor for tourism. The research method used in this paper is interviews and relevant written sources. The goal is that this cultural heritage can continue to be preserved and continue to be an icon for North Sumatra Provin